2018
DOI: 10.1080/09168451.2017.1398068
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of oxidative stress biomarkers

Abstract: Oxidative stress may cause a wide variety of free radical reactions to produce deleterious modifications in membranes, proteins, enzymes, and DNA. Reactive Oxygen Species (ROS) generated by myeloperoxidase (MPO) can induce lipid peroxidation and also play an important role in the generation of reactive chlorinating and brominating species. As the universal biomarkers, chemical, and immunochemical approach on oxidatively modified and halogenated tyrosines has been carried out. As amido-type adduct biomarkers, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Moreover, an elevated level of NO—a reactive free radical—is known to induce nitrosative stress that subsequently damages cellular lipids, nucleic acids and proteins after diminishing the antioxidant defence mechanisms (Moldogazieva, Mokhosoev, Feldman, & Lutsenko, 2018; Taysi, Tascan, Ugur, & Demir, 2019). Increased MPO activity is associated with the excessive free radical generation and oxidative stress (Ndrepepa, 2019; Osawa, 2018). The current study showed that diclofenac administration alone increased MPO activity and NO level in testes and epididymis of treated rats, thus implying the involvement of nitrosative and oxidative stress in the toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an elevated level of NO—a reactive free radical—is known to induce nitrosative stress that subsequently damages cellular lipids, nucleic acids and proteins after diminishing the antioxidant defence mechanisms (Moldogazieva, Mokhosoev, Feldman, & Lutsenko, 2018; Taysi, Tascan, Ugur, & Demir, 2019). Increased MPO activity is associated with the excessive free radical generation and oxidative stress (Ndrepepa, 2019; Osawa, 2018). The current study showed that diclofenac administration alone increased MPO activity and NO level in testes and epididymis of treated rats, thus implying the involvement of nitrosative and oxidative stress in the toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Some of its biotoxic effects could be mediated through the attack of generative reactive oxygen species on some target organs such as the liver, kidney, heart, and brain. When the effects of free radicals are not mitigated in cells, oxidative stress occurs (He et al, 2017;Osawa, 2018). Some of the biomarkers of oxidative stress are catalase, malondialdehyde, and superoxide dismutase (Okolie & Iroanya, 2003;Petkovic et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(3,4) While WBCs are essential for immunity, they are also major endogenous oxidants that may cause chronic inflammation. (5)(6)(7)(8) WBCs are related to various disorders, including arteriosclerosis, (9)(10)(11) neurodegenerative diseases, (12) autoimmune diseases, (13) and cancer, (14,15) but the relationships between each disease and their ability to produce ROS and hROS are not well understood. (9)(10)(11)(12)(13)(14)(15) We have developed monitoring systems for ROS (CL-O 2…”
mentioning
confidence: 99%